The occupation of the Late Initial Period (1100/1000 – 800 BC) and the Early Horizon (800-500/400 BC) in Huanchaco, north coast of Peru - Prieto, Gabriel (2022)
This paper introduces the first results of the archaeological research carried out at the Sector José Olaya – Sitio Iglesia Colonial de Huanchaco. The excavations yielded occupations associated with the Late Initial Period and the Early Horizon. The paper describes the occupations, burials, shellfish, and ceramic identified. The latter is also studied through petrographic analysis done on selected samples. Finally, a stratigraphic study plus the aid of 11 AMS dates, allowed to build a local chronology divided into three subphases: José Olaya 1 (1000-800 B.C.), José Olaya 2 (800-600 B.C.) y José Olaya 3 (600-400 B.C.).